Methodology of Modern Technologies of Teaching Foreign Languages (Eurasian Journal of Humanities and Social Sciences, 2023)
The article deals with interactive methods of teaching English. The purpose of introducing innovative methods of teaching a foreign language into the educational process is not just the accumulation of knowledge and skills, but the constant enrichment of creative experience, the formation of a mechanism for self-organization and self-realization of each student, increasing his/her learning motivation.